Elucidating the mechanism of action of Centella asiatica ethanolic extract and triterpenoids as a potential anti-leukaemic agent through the integration of in silico and in vitro studies / Norodiyah Othman - Othman, Norodiyah (2022)
Centella asiatica (C. asiatica), locally known as 'pegaga', is a herb used in traditional Chinese medicine to treat various diseases, including cancer. There is, however, no information on its potential anti-leukaemic activity. Thus, this study investigated the underlying mechanism of anti-leukaemic activity of C. asiatica ethanolic extract and triterpenoids (madecassoside; ME, asiaticoside; AE, madecassic acid; MA, asiatic acid; AA) on human CCRF-CEM T-acute lymphoblastic leukaemia (T-ALL) cells through in silico and in vitro methods. A ligand-based target prediction model comprising 26 leukaemia-related targets and 26,540 compounds was first built using a random forest algorithm. The model was validated through internal and external validation. Molecular docking was then performed on the targets predicted for the triterpenoids. The in vitro anti-proliferative activity was evaluated by assessing the cell apoptosis rate using annexin-V flowcytometry. The intracellular reactive oxygen species (ROS) level and mitochondrial membrane change (MMP) were measured using fluorescence analysis. At the molecular level, the gene expression profile was assessed by microarray, followed by an analysis of protein-protein interaction and gene enrichment functional analysis. In addition, the protein expression level of the apoptosis-related gene was determined using western blot analysis. The built prediction model, named the Leuk- RP model, showed an average sensitivity, specificity and accuracy of 87.4%, 95.0% and 91.8%), respectively. In the external validation, the model showed an average sensitivity, specificity and accuracy of 89.8%>, 87.5% and 81.9%, respectively. The triterpenoids were predicted to bind to SLC29A1, TNFa, and NR3C1 with different scores. Docking results demonstrated that the triterpenoids could bind to TNFa active site, with binding energies ranging from -9.0 to -9.5 kcal/mol.